1967
DOI: 10.1002/jcp.1040690208
|View full text |Cite
|
Sign up to set email alerts
|

A cytological study of the capacity for differentiation of normal hemopoietic colony‐forming cells

Abstract: A two-stage procedure has been used to obtain hemopoietic spleen colonies derived from single precursor cells containing radiation-induced chromosomal markers. Of a total of 46 colonies examined, 17 were found to contain cells with abnormal karyotypes. In each of the 17 marked colonies, 90% or more of the dividing cells in the colony carried the same marker. Cell suspensions prepared from each of the individual colonies were tested for their content of dividing cells possessing recognizable differentiated func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
84
1
6

Year Published

1970
1970
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(97 citation statements)
references
References 12 publications
5
84
1
6
Order By: Relevance
“…The finding that 5-10% of bone marrow cells were induced to differentiate by extremely low concentrations of pure thymin suggested that these cells were stem cells with appropriate receptors, and thus already committed to eventual thymocyte differentiation. This large population of committed cells would be distinct from the totipotent hematopoietic stem cells, which make up less than 0.1% of the cells in the murine bone marrow (22). Using crude thymus extracts, Komuro and Boyse (8) also demonstrated this large population of mouse hematopoietic cells susceptible to differentiation by a thymus-inducing factor.…”
Section: Discussionmentioning
confidence: 99%
“…The finding that 5-10% of bone marrow cells were induced to differentiate by extremely low concentrations of pure thymin suggested that these cells were stem cells with appropriate receptors, and thus already committed to eventual thymocyte differentiation. This large population of committed cells would be distinct from the totipotent hematopoietic stem cells, which make up less than 0.1% of the cells in the murine bone marrow (22). Using crude thymus extracts, Komuro and Boyse (8) also demonstrated this large population of mouse hematopoietic cells susceptible to differentiation by a thymus-inducing factor.…”
Section: Discussionmentioning
confidence: 99%
“…Animals were killed on days 1 to 4,8,12,16, and 20 after irradiation for histologic analyses. Morphologic analysis of whole animal sections stained with hematoxylin and eosin over 0 Gy to 45 Gy showed an apparent threshold dose of 20 Gy that specifically ablated the majority of cells within hematopoietic tissues.…”
Section: Histologic Analyses Following Irradiationmentioning
confidence: 99%
“…Although humoral factors produced from these tissues were initially proposed to be the radioprotective elements, 2 subsequent studies showed that survival correlated with the level of hematopoietic repopulation by donor-derived cells. [5][6][7][8] Pioneering studies by Till and McCulloch and colleagues showed that donor bone marrow contained rare cells that generated clonal, macroscopic spleen colonies, 9,10 a fraction of which regenerated spleen colonies 11 or repopulated multilineage hematopoiesis 12 in hosts receiving serial transplants. These experiments led to the concept of the hematopoietic stem cell (HSC).…”
Section: Introductionmentioning
confidence: 99%
“…(Received for publication 5 March 1974) There is general agreement that the mature cells of the blood of mammals arise from a pluripotent hemopoietic stem cell (1)(2)(3)(4). This cell is defined by ability to form spleen colonies after injection into lethally irradiated mice (5) and is thus called a spleen colony-forming unit or CFU-s. Colonies of myeloid cells can be formed in vitro (6,3) and the cells which give rise to these colonies (CFU-c) differ in many properties from the CFU-s.…”
mentioning
confidence: 99%
“…This cell is defined by ability to form spleen colonies after injection into lethally irradiated mice (5) and is thus called a spleen colony-forming unit or CFU-s. Colonies of myeloid cells can be formed in vitro (6,3) and the cells which give rise to these colonies (CFU-c) differ in many properties from the CFU-s. The CFU-c appear to be slightly denser (8,9), have a higher sedimentation rate, (8) and have a larger proportion of cells in S phase of the cell cycle than CFU-s (10,11).…”
mentioning
confidence: 99%